LOAD ANALYSIS AND OPTIMUM DESIGN OF THE SUPPORTING PLATFORM FOR GASOLINE HYDROGENATION UNIT - DONG Min; MA ChangFei; GUO XinXin; LI Xiang; XIA ChenLiang; LIAN XiaoShuo (Jixie qiangdu)
Gasoline hydrogenation is an important processing technology in petrochemical production. The majority of supporting platforms of production equipment in the form of steel structure,which the strength and stiffness are very important to the production safety. The finite element model is established by ANSYS Workbench software. The static load and ground motion load response analysis are carried out according to the actual force of the support platform,and optimize the design of supporting platform. Regarding both the lower weight of the 2th and 3th layers of H type steel and lower value of the deformation which under static load as the objectives of optimizing design,and the section size of the 2th and 3th layers of H type steel as the design variable. Total amount of steel for supporting platform is reduced by 16. 8% than before,and the production cost reduced obviously. The stress value of the optimized frame steel structure which under the ground motion load is reduced by 4. 2%.